2018
DOI: 10.1002/cpp.2342
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive virtual reality system for the treatment of adjustment disorder and complicated grief: 1‐year follow‐up efficacy data

Abstract: Adjustment disorder (AD) and complicated grief (CG) are serious mental conditions that have a high prevalence and are associated with significant impairments in social and work functioning. Recently, these categories have been better specified in the new ICD‐11 proposal. Empirical research on the efficacy of treatments for these problems is scarce. This study aims to offer long‐term efficacy data from a between‐groups controlled study that compares two treatment conditions (AD‐protocol applied in a traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 70 publications
4
13
0
3
Order By: Relevance
“…The high drop-out rates from this trial (86%) prevent firm conclusions from being drawn. A second study targeted ICD-10 and DSM-IV adjustment disorder, and compared a face-to-face and virtual reality delivered cognitive behavioural therapy (CBT) to the waitlist [56]. Both the face-to-face and virtual reality CBT resulted in significantly greater improvements to adjustment disorder relative to the wait-list controls at pre/post treatment.…”
Section: Treatment and Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high drop-out rates from this trial (86%) prevent firm conclusions from being drawn. A second study targeted ICD-10 and DSM-IV adjustment disorder, and compared a face-to-face and virtual reality delivered cognitive behavioural therapy (CBT) to the waitlist [56]. Both the face-to-face and virtual reality CBT resulted in significantly greater improvements to adjustment disorder relative to the wait-list controls at pre/post treatment.…”
Section: Treatment and Interventionmentioning
confidence: 99%
“…In summary, the emergence of clear diagnostic criteria with ICD-11 has finally presented the opportunity for new treatment options to be developed and tested. Several emerging treatment options have utilised the internet to complement the therapeutic approach, which is likely to be appealing to individuals with sub-clinical problems such as adjustment disorder [56]. Additionally, treatments that are brief and scalable may be appropriate for the treatment of adjustment disorder.…”
Section: Treatment and Interventionmentioning
confidence: 99%
“…Specifically, a flexible VR system called EMMA’s World was developed to assist in achieving this goal [22]. Results from a randomized controlled trial showed that the protocol has comparable effects with and without the use of the VR system, and the VR group showed slight superiority only at the 12-month follow-up [23]. However, VR can provide additional benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, estos podrían ser algunos de los motivos por los cuales Brodbeck et al (2017) incluyeran en su estudio pacientes con este perfil. En un estudio reciente realizado por Quero et al (2019) se encontró una eficacia similar de un TCC aplicado cara a cara y apoyado por realidad virtual, mostrándose ambas condiciones de intervención superiores a un grupo control lista de espera en el tratamiento de trastornos relacionados con estrés (trastornos adaptativos y TDP). El evento estresante sufrido en el 25.93% de los pacientes fue una ruptura sentimental o divorcio.…”
Section: Discussionunclassified